Association between prenatal exposure to industrial air pollution and onset of early childhood ear infection in China. (May 2017) - Deng, Qihong; Lu, Chan; Li, Yuguo; Chen, Lv; He, Yanrong; Sundell, Jan; Norbäck, Dan
Abstract: Background: Otitis media (OM) is a common infection in early childhood with repeated attacks that lead to long-term complications and sequelae, but its etiology still remains unclear. Objective: To examine the association between early life exposure to air pollution and childhood OM, with the purpose of identifying critical windows of exposure and key components of air pollution in the development of OM. Methods: We conducted a prospective cohort study of 1617 children aged 3–4 years in Changsha, China (2011–2012). The prevalence of OM was assessed by a questionnaire administered by the parents. Individual exposures to nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ) and particulate matter with an aerodynamic diameter ≤ 10 μm (PM10 ) during prenatal, postnatal, and current windows were estimated using the measured concentrations at monitoring stations. We used logistic regression model to examine the OM risk in terms of odds ratio (OR) and 95% confidence interval (CI) for exposure to different air pollutants during different timing windows, adjusting for covariates, multi-pollutants, and multi-windows. Results: Life-time prevalence of doctor-diagnosed OM in preschool children in Changsha was 7.3%. Childhood OM was associated only with prenatal exposure to the industrial air pollution with adjusted OR (95% CI) = 1.44 (1.09–1.88) for a 27 μg/m3 increase in SO2, particularly during the first trimester of pregnancy. We further found that prenatal SO2 exposure was not associated with the repeated attacks but was associated with the onset of OM, adjusted OR (95% CI) = 1.47 (1.10–1.96). The association between prenatal SO2 exposure and early childhood OM was robust after adjusting for other pollutants and windows. Sensitivity analysis indicated that the association was stronger in females, children with parental atopy, and children living in houses with cockroaches, new redecoration, and condensation on window pane during winter. Conclusion: We provide new evidence that prenatal exposure to industrial air pollution is associated with early childhood OM in China and may contribute to the onset of childhood OM. Our findings are helpful in developing more effective preventative strategies for childhood OM. Graphical abstract: Highlights: The effect of prenatal exposure to air pollution on childhood otitis media (OM) is not known. Prenatal exposure to industrial air pollution is associated with OM onset but not recurrence. We provide evidence that industrial air pollution causes childhood ear infection in China. Our findings support the hypothesis that childhood OM has fetal origins.